A C-type lectin (LvCTL4) from Litopenaeus vannamei is a downstream molecule of the NF-κB signaling pathway and participates in antibacterial immune response. Issue 1 (March 2015) - Li, Haoyang; Chen, Yonggui; Li, Ming; Wang, Sheng; Zuo, Hongliang; Xu, Xiaopeng; Weng, Shaoping; He, Jianguo; Li, Chaozheng
Abstract C-type lectins (CTLs) play multiple roles in innate immune defense against invading pathogens in both vertebrates and invertebrates. In this study, a new C-type lectin gene from pacific white shrimp Litopenaeus vannamei (designated as LvCTL4) was cloned by rapid amplification of the cDNA ends (RACE) method. The full-length cDNA of LvCTL4 was 563 bp with open reading frame (ORF) of 471 bp encoding a polypeptide of 156 amino acids, including a putative signal sequence and a single C-type lectin-like domain (CTLD). The CTLD of 137 amino acid residues contained a mutated 'EPA' (Glu121-Pro122-Ala123) motif in the calcium-binding site 2 and three conserved disulfide bonds involved in structure maintenance. Tissue expression analysis showed LvCTL4 was ubiquitously distributed with high levels in gill, intestine, epithelium and hepatopancreas. The expression of LvCTL4 in gill was up-regulated in response to Vibrio parahaemolyticus challenge. RNAi knock-down of the LvCTL4 gene significantly increased mortality after V. parahaemolyticus infection. A 103 bp 5′ flanking promoter sequence was obtained using the genome walking method and it contained a conserved NF-κB binding motif. Dual-Luciferase assay showed both LvDorsal and LvRelish could up regulate the promoter activity of LvCTL4. This is the first report that a shrimp C-type lectin can be regulated by both LvDorsal and LvRelish. These findings provided novel insights into the regulation of shrimp CTLs expression.